Analysis of the Influence of Tourism Development on Accommodation and Provision Business Field Sector Food and Drink in NTB Province 2009-2023 - Ita Ayu Febrianti; Mansur Afifi; Baiq Ismiwati (West Science Social and Humanities Studies, 2024)
The purpose of this study is to analyze the influence of the number of tourists, investment in the tourism sector and the length of tourist stay on the business sector of providing accommodation and food and beverages in NTB Province both simultaneously and precisely. This research uses secondary data taken from the official website of the Central Statistics Agency of West Nusa Tenggara Province and the Culture and Tourism Office in 2009-2023. This study uses a data analysis method in the form of multiple linear regression analysis using the SPSS application as an analysis tool. The results of this study show that the variables of the number of tourists, investment in the tourism sector, and the length of stay of tourists simultaneously affect the business sector of accommodation and food and beverage in NTB Province. Partially, the variable of the number of tourists Hhas a positive and significant effect, investment in the tourism sector has a negative and insignificant effect and the length of stay of tourists has a positive and significant effect on the business sector of providing accommodation and food and beverages in NTB Province in 2009-2023.